The Endoscopic Anatomy of the External Acoustic Meatus and of the Middle Ear in Dry Temporal Bones: A Study Conducted Using Digital and Mobile Device Technology - Gaspar-Sobrinho, Fernando P.; Trzan, Aline L. S.; Uzeda, Sandra de Q.; Nogueira, Joao Flavio (International Archives of Otorhinolaryngology, 2022)
Introduction The endoscopic anatomy of the middle ear (ME) and of the external acoustic meatus (EAM) has been described in cadavers, in fresh temporal bones, or in vivo using conventional video recording, but not in dry bones or using an alternative inspection and recording technique.Objective To study the anatomy of the ME and of the EAM in dry temporal bones using a smartphone-endoscope system.Methods The EAM and the ME were studied in dry temporal bones using an endoscopic transcanal approach with a telescope connected to a smartphone (M-scope mobile endoscope app and adaptador, GBEF Telefonia, São Paulo, SP, Brazil).Results Out of 50 specimens, 2 had exostosis of the EAM and 3 contained remains of the tympanic membrane. The anterior wall of the EAM was prominent in 10/48 specimens (20.8%). Ossicles were seen in 13/45 (28.8%), stapes at the oval window were seen in 12/45 (26.6%), and the incus was seen in 1/45 (2.2%) specimens. The facial canal was open and protruding in 15/45 (33.3%) and in 7/45 (15.5%) specimens, respectively. Of the 45 MEs evaluated, type A was predominant for finiculus (93.3%), subiculum (100%), and ponticulus (95.6%). The rest were type B. None was classified as type C. According to its position in relation to the round window, the fustis was classified into type A (68.9%) or B (31.1%). The pyramidal eminence, the bony portion of the Eustachian tube, the semicanal of the tensor tympani muscle, and the cochleariform process were visualized completely or partially in all cases.Conclusion The use of a smartphone-based endoscopic transcanal procedure in dry temporal bones allowed the evaluation of anatomical variations in the EAM and in the ME.
Keywords: anatomy of the middle ear; temporal bone; endoscopic surgical procedure; otologic surgical procedure; external acoustic meatus